L-Threonine production from whey and fish hydrolysate by E. coli ATCC® 21277TM (2023)
ABSTRACT: In this work production of L-threonine by Escherichia coli ATCC® 21277TM has been studied using a mixture of alternative low-cost substrates, which are recognized to be a major pollution problem. Whey was used as the primary carbon source, whereas Red Tilapia (Oreochromis sp.) viscera hydrolysates constituted the nitrogen source. A Box-Behnken Design was used for optimizing L-threonine and biomass production, using temperature and glucose, whey, and Red Tilapia (Oreochromis sp.) viscera hydrolysate contents as factors. Results indicate that biomass production is affected by the concentration of hydrolysate and temperature. On the other hand, L-threonine production is affected by concentration of whey, hydrolysate, and temperature. In this context, it was possible to maximize L-threonine production, but with a detriment on biomass production. The optimal conditions for biomass and L-threonine maximization (after 24 h) were identified and validated experimentally, resulting in biomass and L-threonine production of 0.767 g/L and 0.406 g/L, respectively. This work has shown the technical feasibility of using whey and Red Tilapia (Oreochromis sp.) viscera hydrolysates for the production of L-threonine by E. coli ATCC® 21277TM. Finally, the complications associated to the use of these low-cost complex substrates for the production of L-threonine by E. coli, suggest that more in detail studies (i.e. at the metabolic level) are required in order to propose strategies to increase the process productivity, before its scale up. This is a first step in our long-term goal of developing a production process for i) dealing with the pollution problems caused by those wastes, and ii) strengthen the milk and fish industries which are important poles of the Colombian economy.